Graphite N–C–P dominated three-dimensional nitrogen and phosphorus co-doped holey graphene foams as high-efficiency electrocatalysts for Zn–air batteries. Issue 36 (9th September 2019) - Ge, Liping; Wang, Dan; Yang, Peixia; Xu, Hao; Xiao, Lihui; Zhang, Guo-Xu; Lu, Xiangyu; Duan, Zhenzhen; Meng, Fan; Zhang, Jinqiu; An, Maozhong
Abstract : A C atom with a positive charge in the graphite N–C–P structure is the dominating ORR active site in N, P-HGFs. Abstract : The search for metal-free catalysts for oxygen reduction reactions (ORRs) in energy storage and conversion devices, such as fuel cells and metal–air batteries, is highly desirable but challenging. Here, we have designed and synthesized controllable 3D nitrogen and phosphorous co-doped holey graphene foams (N, P-HGFs) as a high-efficiency ORR catalyst through structural regulation and electronic engineering. The obtained catalyst shows a half-wave potential of 0.865 V in alkaline electrolytes. It is found that Zn–air batteries with the N, P-HGFs-1000 air electrode exhibit excellent discharge performance and durability. Our study suggests that the remarkable ORR performance of N, P co-doped graphene is mainly due to the graphite N–C–P structure, where an enhanced charge density and increased HOMO energy level are confirmed by both experimental results and theoretical density-functional theory calculations.